KEPASTIAN HUKUM DALAM UPAYA PERLINDUNGAN TERHADAP PENGUASAAN TANAH TIMBUL (AANSILBBING) OLEH MASYARAKAT - Devi Siti Hamzah Marpaung (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
The Land Arises (aanslibbing) is a new natural resource that is economically potential for agriculture and farming and even industrial activities that can lead to ownership and ownership of The Land Arises. Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (LoGA) as a basic regulation, only regulates the principles or main problems in outline. The research method used is normative legal research, namely legal research carried out by analyzing legal norms and rules contained in legislation, namely Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles and court decisions, as well as doctrines. The results of the study, the legal certainty of land ownership rights (aansilbbing) will be recognized as legitimate ownership, namely through the registration of land and obtaining permits directly from government officials namely the Head of the local Land Office, giving clear boundaries without being questioned by any party also paying compensation income into the village treasury for the issuance of written evidence by the local village authorities regarding the control of the land. Then, the effort to obtain protection for land arises also requires the implementation of land registration activities that make it possible for the holders of land rights to easily prove their rights to the land under their control and for the parties concerned.